2022
DOI: 10.1155/2022/8188404
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA-AK046375 Upregulates Metallothionein-2 by Sequestering miR-491-5p to Relieve the Brain Oxidative Stress Burden after Traumatic Brain Injury

Abstract: We previously discovered that traumatic brain injury (TBI) induces significant perturbations in long noncoding RNA (lncRNA) levels in the mouse cerebral cortex, and lncRNA-AK046375 is one of the most significantly changed lncRNAs after TBI. lncRNA-AK046375 overexpression and knockdown models were successfully constructed both in vitro and in vivo. In cultured primary cortical neurons and astrocytes, lncRNA-AK046375 sequestered miR-491-5p, thereby enhancing the expression of metallothionein-2 (MT2), which ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…These nine subpopulations of T cells, especially Tregs, may be involved in protecting apoptosis and suppressing proinflammatory cytokines under high stress, which provides a novel insight into the treatment of ACS. In contrast, the MT family, which was found to have a role in the reduction of oxidative damage and apoptosis in animal models and was involved in the binding of a large number of heavy metal ions such as zinc ions, copper ions, or cadmium ions ( 58 , 59 ), was down-regulated in nine subsets ( 60 62 ). We suppose that HSP , MT , or the ratio of HSP to MT may be an important disease biomarker in the diagnosis of ACS, or maybe a potential key factor of ACS that is worthy of study at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…These nine subpopulations of T cells, especially Tregs, may be involved in protecting apoptosis and suppressing proinflammatory cytokines under high stress, which provides a novel insight into the treatment of ACS. In contrast, the MT family, which was found to have a role in the reduction of oxidative damage and apoptosis in animal models and was involved in the binding of a large number of heavy metal ions such as zinc ions, copper ions, or cadmium ions ( 58 , 59 ), was down-regulated in nine subsets ( 60 62 ). We suppose that HSP , MT , or the ratio of HSP to MT may be an important disease biomarker in the diagnosis of ACS, or maybe a potential key factor of ACS that is worthy of study at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lncRNA FRMD6-AS1 expression was elevated in activated HSC-T6 cells, and knockdown of FRMD6-AS1 increased iron miR-491-5p can be declined by lncRNAs in cancers, brain oxidative stress after brain injury, and atherosclerosis. 41,42 By competitively binding with miR-491-5p, lncRNAs, such as lncRNA AK046375, LINC02381 and lncRNA LBX2-AS1, can modulate the progression cancers and oxidative stress. 41,42 In addition, miR-491-5p exerts Several target genes of miR-491-5p, including emilin 1, TP53 and metallothionein-2, could be dramatically repressed by miR-491-5p via binding to 3' UTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the main ways of lncRNAs on regulating the expressions of mRNAs through influencing the expression and/or chromatin state of nearby genes and interacting with proteins and/or other RNA molecules such as miRNAs ( Marchese et al, 2017 ). Recent study have revealed that downregulation of miR-491-5p promotes neovascularization after TBI ( Tang et al, 2022b ), and lncRNA-AK046375 enhances MT2 expression by sequestering miR-491-5p, ultimately strengthening antioxidant activity, which ameliorates neurological deficits post-TBI ( Tang et al, 2022a ). These studies show the prospect of ceRNA regulation mechanism in TBI research.…”
Section: Discussionmentioning
confidence: 99%